QUALITY OF DIRECT CUSTOMER COMPLAINTS SERVICE IN DELTA TIRTA REGIONAL DRINKING WATER COMPANIES IN SIDOARJO DISTRICT, SIDOARJO REGENCY - Reyndi Rusmanjaya; Agus Widiyarta (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The quality of public services can be used as a benchmark for the results of the government's performance itself has been going well or there are still things that need to be addressed. Clean water service is a product of the type of service goods that are grouped in the form of provision or management of a physical form including distribution and direct delivery to consumers in one system. PDAM